1975
DOI: 10.1901/jeab.1975.24-59
|View full text |Cite
|
Sign up to set email alerts
|

SOME VARIABLES AFFECTING RATE OF KEY PECKING DURING RESPONSE‐INDEPENDENT PROCEDURES (AUTOSHAPING)1

Abstract: Rate of key pecking by pigeons subjected to response-independent procedures in which a stimulus on the response key preceded food presentation was investigated in eight experiments. Color and shape of the stimulus, duration of the stimulus, probability of food following the stimulus, duration of the intertrial interval, and duration of food presentation were varied separately and in combination. All variables studied, except color and shape of the stimulus, had a reliable effect on pecking rate, but some varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
46
4

Year Published

1977
1977
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 13 publications
9
46
4
Order By: Relevance
“…But Gonzalez also used a complex procedure, yoked across several birds to reduce responding during the ITI, and this may have eliminated the CRF/PRF differences found here and by Gibbon et al (1980). Autoshaping studies that have compared within-subjects PRF and CRF schedules have reported no acquisition rate differences (Gonzalez, 1974;Perkins et al, 1975;Picker 76.24, p < .001]. In extinction, this preference for the CRF stimulus gave way to a preference for the PRF stimulus using the first two measures via a significant schedule x sessions interaction [F(4,24) = 3.65, p < .05, location of first peck; F(4,24) = 3.47, p < .05, percent trials with a peck], but no significant interaction was found for percent total responses.…”
Section: Phasementioning
confidence: 90%
See 1 more Smart Citation
“…But Gonzalez also used a complex procedure, yoked across several birds to reduce responding during the ITI, and this may have eliminated the CRF/PRF differences found here and by Gibbon et al (1980). Autoshaping studies that have compared within-subjects PRF and CRF schedules have reported no acquisition rate differences (Gonzalez, 1974;Perkins et al, 1975;Picker 76.24, p < .001]. In extinction, this preference for the CRF stimulus gave way to a preference for the PRF stimulus using the first two measures via a significant schedule x sessions interaction [F(4,24) = 3.65, p < .05, location of first peck; F(4,24) = 3.47, p < .05, percent trials with a peck], but no significant interaction was found for percent total responses.…”
Section: Phasementioning
confidence: 90%
“…However, this is clearly not always the case. Birds will discriminate a 0% stimulus from a stimulus that does predict food (Perkins et al, 1975). Furthermore, Picker and Poling (1982) found that single-stimulus performance with CRF and PRF schedules did not differ even after extensive training, but their animals demonstrated a clear discrimination on choice trials.…”
mentioning
confidence: 98%
“…However, a more traditional measure of strength of keypeck responding-rate of maintained responding-shows less sensitivity to these variables (Balsam & Payne, 1979;Crawford, Steirn, & Pavlik, 1985;Gonzalez, 1974;Kay, Hemmes, & Brown, 1984;Lucas, Deich, & Wasserman, 1981; Newlin & LoLordo, 1976;O'Connell & Rashotte, 1982;Perkins et al, 1975).…”
mentioning
confidence: 99%
“…The present experiment is addressed to another traditional variable in classical conditioning, partial reinforcement. There is evidence that partial reinforcement exerts effects on maintained responding (Gonzalez, 1973(Gonzalez, , 1974Perkins, Beavers, Hancock, Hemmendinger, Hemmendinger, & Ricci, 1975;Schwartz & Williams, 1972;Wasserman, 1974;Wasserman, Hunter, Gutowski, & Bader, 1975). The effect of partial reinforcement on acquisition of autoshaped responding has received less parametric study.…”
mentioning
confidence: 99%